Fiscal policy cycles and the exchange regime in developing countries - Ludger Schuknecht (World Trade Organization (WTO), 1998)
The paper studies empirically fiscal policies around elections in 25 developing countries as affected by the exchange regime. It is argued that countries with flexible exchange regimes are less likely to engage in expansionary fiscal policies before elections because such policies can result in devaluations and inflation which affects government popularity adversely. The empirical results show that governments indeed try to improve their re-election prospects with the help of expansionary fiscal policies only in countries with fixed exchange rates and adequate reserve levels. For some countries, this raises doubts about the usefulness of fixed exchange rates for stabilizing the macro economy, unless reforms of the institutional framework reduce the scope for election-oriented fiscal expansion.
Keywords: F41; E62; H62; 330; Elections; political business cycles; fiscal policies; deficits; developing countries